The rising pressure of global water shortages - Eliasson, Jan (Nature (London), 2015)
In recent months, it has directed its operations to Iraqi hydroelectric dams - in particular, the Mosul dam. The Water Convention that was forged under the auspices of the United Nations Economic Commission for Europe in 1992 is one such notable agreement.